THE DEGREE OF COMPANY VULNERABILITY USING ALTMAN MODEL: A SURVEY OF PUBLIC LISTED COMPANIES IN INDONESIA - Marko S. Hermawan; Junius Tirok; Dharma S. Dawis (Journal of Applied Finance & Accounting, 2010)
This research is purposed to analyze the degree of vulnerability of a company’s performance. From the financial report produced, investor will analyze the level of its performance. There are several variables of defining the performances, in which they are used to distinguish the degree of vulnerability. This level of degree affects investor’s decision on company’s performance. The object of this research, after taking relevant data from years 2006- 2008 published annual financial reports, there are 184 public companies listed in Indonesian Stock Exchange that are qualified in the analysis procedure. The Altman (1993) model of Z-score formula is used to define variables reflecting in a company performance, in which is classified into three-zone index (safe zone, grey zone and distress zone). This research has found that more companies lie in the grey and distress zone. Amongst the safe zone companies are Mining Industry and the lowest degree is the Infrastructure Industry. Also, a trend of decreasing performance occurred during 2008. There are possible reasons that might result in the performance of the industries. This result of research will benefit for investors in considering investing in Indonesian companies.